IMPLEMENTING COOPERATIVE LEARNING TO IMPROVE STUDENTS’ WRITING ABILITY AT 8 GRADE IN SMP NEGERI 4 BITUNG - Saleh, Reina; Pelenkahu, Noldy; Muntuuntu, Meity (JoTELL : Journal of Teaching English, Linguistics, and Literature, 2022)
This study aimed to determine whether cooperative learning can improve students’ writing ability at grade 8 in SMP Negeri 4 Bitung. This research design using quantitative method. The samples in this study were students of class 8A as the control class and 8D as the experimental class. Each sample consists of 30 students and the total of sample in this study were 60 students in academic year 2021/2022. The collected data techniques were pre-test and post-test and the instrument used to measure learning outcomes was a written test in the form of an essay. The post-test data analysis of the two groups used the independent t-test. The results of the study obtained that Tcount was 1.966422631 and Ttable at the significant level of 0.05 was 1.6991, then Tcount > Ttable.Thus, it means that H0 is rejected and H1 is accepted. So it can be concluded that there was a significant effect from the implementing cooperative learning to improve student writing ability on the learning outcomes of 8th grade at SMP Negeri 4 Bitung